2021
DOI: 10.1007/s40200-021-00835-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of antidiabetic therapy with shortened telomere length in middle-aged Type 2 diabetic patients

Abstract: Introduction A wide range of antidiabetic therapies have been developed to manage diabetes and limit its lifespan but each of them have adverse long-term drug reactions. This study was performed for the investigation of the possible association of antidiabetic therapy with shortened telomere length in middle-aged Type 2 diabetic patients. Materials and methodsThe subjects in this case-control study included 100 non-diabetic patients and 300 patients with Type 2 diabetes with ages in the range of 30-50 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…61,62 Al-Thuwaini et al suggested that the prolongation of TL in patients with T2DM with glyburide may be caused by a decrease in oxidative stress levels due to good glycemic control. 33 As mentioned earlier, oxidative stress induced by hyperglycemia has been found to accelerate telomere shortening. 7 Additionally, some scholars have highlighted that oxidative stress can inhibit the activity of telomerase.…”
Section: Sulfonylureamentioning
confidence: 83%
See 3 more Smart Citations
“…61,62 Al-Thuwaini et al suggested that the prolongation of TL in patients with T2DM with glyburide may be caused by a decrease in oxidative stress levels due to good glycemic control. 33 As mentioned earlier, oxidative stress induced by hyperglycemia has been found to accelerate telomere shortening. 7 Additionally, some scholars have highlighted that oxidative stress can inhibit the activity of telomerase.…”
Section: Sulfonylureamentioning
confidence: 83%
“…Logistic regression analysis showed that only insulin use (OR: 17.355, 95% CI: 2.659 to 35.627, p=0.013) and LDL-C level (OR: 3.493, 95% CI: 1.599 to 10.063, p=0.007) were independent predictors of telomere shortening. The aforementioned case-control study 33 found that telomere shortening was 3 times higher in insulin-treated patients with T2DM (logistic regression analysis, estimate: −3.41, p=0.001). A cross-sectional study 35 by AlDehaini et al found no significant difference in leukocyte TL among patients treated with metformin alone, insulin alone, or a combination of the both.…”
Section: Exogenous Insulinmentioning
confidence: 96%
See 2 more Smart Citations
“…Glibenclamide has been found to remarkably decrease the telomere shortening rate. This may be due to the fact that glibenclamide stimulates insulin secretion from pancreatic β-cells and reduces free fatty acid concentrations [ 40 ]. A randomized controlled trial reported a significant improvement in glucose control, reduced insulin resistance, and elongated telomere length in T2DM patients treated with sitagliptin for 2 months.…”
Section: Discussionmentioning
confidence: 99%